Finding a suitable separation condition for TLC/FTIR analysis by using multiple-narrow-band TLC technique. Issue 28 (24th February 2015) - Jiang, Ye; Kang, Xiaoyan; Gao, Danqing; He, Anqi; Guo, Ran; Fan, Xiaokun; Zhai, Yanjun; Xia, Jinming; Xu, Yizhuang; Noda, Isao; Wu, Jinguang
Abstract : A multiple-narrow-band TLC approach is proposed to find suitable solvent for TLC analysis in a high-throughput manner. Abstract : Thin layer chromatography (TLC) coupled with infrared spectroscopic technique has great advantages in the separation and identification of different components in a mixture. However, determination of suitable separation condition is a tedious task. To improve the efficiency of finding suitable separation conditions, we propose a multi-narrow-band TLC approach. In this approach, a TLC plate containing several parallel narrow bands was utilized. In experiment, different pure substance was added on each of the narrow bands and TLC analysis was performed under same condition. Different substance exhibits different migration distance. Thus, it becomes much easier to separate substances with large difference in migration distance. This approach can be used to find multiple mixed sample pairs in a parallel manner. Consequently, a high-throughput method on selection of suitable mobile phase and separation conditions can be established.